The Use of Noninvasive Mechanical Ventilation for the Treatment of Acute Exacerbations of Copd in Canada - Jennifer Drummond; Brian Rowe; Lawrence Cheung; Irvin Mayers (Canadian Respiratory Journal)
BACKGROUND: Noninvasive mechanical ventilation (NIMV) is accepted as a life-saving treatment for patients presenting to the emergency department and other acute care settings with severe exacerbations of chronic obstructive pulmonary disease (COPD).